Benzimidazole-functionalized fluorescent probe for rapid detection of 2,4,6-trinitrophenol and Ag+ in semiaqueous medium - Wang Bin; Jiang Fan; Zuo Xixi; Ma Jing; Ma Xiangmei (Journal of the Serbian Chemical Society, 2021)
In this study, a simple fluorescent chemosensor with good fluorescence properties was synthesized, and was used to develop a sensitive and selective sensor, for the determination of 2,4,6-trinitrophenol (TNP) and Ag+ in THF/H2O medium, based on the fluorescence quenching mechanism. Fluorescence quenching experiments revealed that the fluorescence intensities of the resulted probe were linear with the concentrations of TNP and Ag+ in the concentration range of 3.0–5.0 and 2.0–5.0 μmol dm-3, with the detection limit of 1.36 and 0.82 μmol dm-3, respectively. At the same time, accompanied with fluorescent color change under 365 nm UV light irradiation. This has demonstrated that the compound can act as a potential candidate for a “naked-eye” rapidly detector for Ag+ and TNP in soils and aquatic systems.